Effect of Short Term Balance Training on Postural Stability in Ice Hockey Players - Pavol Čech (Karolinum Press, 2015)
Postural stability is one of latent factors affecting game performance of an individual to a certain extent. The presented study deals with monitoring changes of postural stability in ice hockey players after eight week's balance training. The screened sample consisted of junior category ice hockey players divided into experimental (n = 8) and reference groups (n = 8). Postural stability was measured using a stabilographic method on the AMTI AccuSwayPLUS force platform. The level of postural stability was assessed in three tests, namely bipedal stance with and without sight control and bipedal stance with reduced proprioception using the parameters of 95% confidence ellipse, path of CoP and mean velocity of CoP. The level of monitored stability parameters did not indicate any significant differences between the groups in any of the tests at the level of significance α = 0.05. Comparing postural stability of the experimental group between pre-test and post-test showed significant differences in the test without sight control and the test with reduced proprioception in lCoP and vCoP parameters (Z = 2.1004; α ˂ 0.05). Regarding the reference group, no significant changes of the level of postural stability between the pre-test and post-test were found in any of the parameters (Z = 0.3652 to 1.8257; α ˃ 0.05).